Stability analysis of a giving up smoking model - Alkhudhari, Zainab; Al-Sheikh, Sarah; Al-Tuwairqi, Salma (International Journal of Applied Mathematical Research, 2014)
In this paper we present and analyze a generalization of the giving up smoking model that was introduced by Sharomi and Gumel [4], in which quitting smoking can be temporary or permanent. In our model, we study a population with peer pressure effect on temporary quitters and we consider also the possibility of temporary quitters becoming permanent quitters and the impact of this transformation on the existence and stability of equilibrium points. Numerical results are given to support the results. Keywords: Smoking model, Smoking generation number, Local stability, Global stability, Second additive compound matrix, Liapunov function.